Grundtvig og myterne - en replik til Flemming Lundgreen-Nielsen - Ægidius, Jens Peter (Grundtvig-Studier, 1996)
Grundtvig and the Myths - A Reply to Fl. Lundgreen-Nielsen By Jens Peter Ægidius Jens Peter Ægidius criticizes Fl. Lundgreen-Nielsen’s interpretation of Grundtvig’s use of the Nordic mythology as imagery, published in Grundtvig Studies 1994. Here Lund-Nielsen proposed the view that Grundtvig’s use of this imagery must be considered a failure. Referring among other things to the use of mythology in the Danish folk high school, Ægidius points out that Lundgreen-Nielsen’s opinion should not remain unchallenged.